A new species of Clinanthus (Amaryllidaceae: Amaryllidoideae: Clinantheae) from Cordillera de los Tarros, Northwest Peru, and notes on related species - Esquerre-Ibañez, Boris; Meerow, Alan W. (Phytotaxa, 2020)
Clinanthus longissimus B. Esquerre & Meerow sp. nov. is described from the Department of Cajamarca in northwest Peru. This new species has affinity with C. coccineus (Ruiz. & Pav.) Meerow, C. incarnatus (Kunth) Meerow and C. variegatus (Ruiz & Pav.) Meerow, from which it can be distinguished mainly by the length of the flower, the continuous floral tube without protuberances, the size of the staminal cup and the color of the tepals. C. longissimus is so far known only from the Province of Cutervo.